Analysis of System Performance Improvement Due to DG Integration on 20kV Feeder Ampelgading: Case Study Using ETAP Simulation - Akbar, Fajar Maulana; Sulistiawati, Irrine Budi; Wartana, I Made (FORTEI Regional VII Jawa Timur, 2025)
The 20 kV Ampelgading feeder, which is integrated with the Ampelgading Hydropower Plant (PLTA) as a Distributed Generation (DG), still faces technical challenges such as low voltage at the downstream part of the network and relatively high active power losses. These issues are mainly caused by the long distribution line of approximately ±180 km and the uneven load distribution, which results in suboptimal power quality. This research aims to analyze the impact of capacitor bank installation on the voltage profile and line losses of the distribution system. The method employed is a simulation using ETAP 21.0.1 software under peak load conditions as the basis of analysis. The improvement strategy is implemented through the Optimal Capacitor Placement (OCP) method, which recommends the installation of 220 kVAR capacitors at Bus 62, Bus 70, and Bus 80 as the optimal locations based on voltage sensitivity analysis. The simulation results indicate that the capacitor bank injection successfully improves the minimum bus voltage from 0.939 p.u. in the base case to 0.973 p.u., ensuring that all buses meet the lower voltage limit standard of 0.95 p.u. Furthermore, total active power losses are reduced from 93.36 kW to 83.37 kW, representing a decrease of approximately 10.7%. These findings demonstrate that the OCP method is an effective technical solution for optimizing the performance of distribution networks, particularly for feeders with geographical and load characteristics similar to the Ampelgading feeder.